Fusobacterium nucleatum exacerbates chronic obstructive pulmonary disease in elastase‐induced emphysematous mice. Issue 3 (30th January 2022) - Suzuki, Ryuta; Kamio, Noriaki; Kaneko, Tadayoshi; Yonehara, Yoshiyuki; Imai, Kenichi
Abstract : Exacerbation of chronic obstructive pulmonary disease (COPD) is associated with disease progression and increased mortality. Periodontal disease is a risk factor for exacerbation of COPD, but little is known about the role of periodontopathic bacteria in this process. Here, we investigated the effects of intratracheal administration of Fusobacterium nucleatum, a periodontopathic bacteria species, on COPD exacerbation in elastase‐induced emphysematous mice. The administration of F. nucleatum to elastase‐treated mice enhanced inflammatory responses, production of alveolar wall destruction factors, progression of emphysema, and recruitment of mucin, all of which are symptoms observed in patients with COPD exacerbation. Hence, we propose that F. nucleatum may play a role in exacerbation of COPD. Abstract : Periodontal disease is a risk factor for chronic obstructive pulmonary disease (COPD) exacerbations. We found that intratracheally administered Fusobacterium nucleatum, a periodontopathic bacterium that increases in saliva when periodontal disease advances, to elastase‐induced emphysematous mice enhances (i) inflammatory responses, (ii) alveolar wall destruction factor production, (iii) emphysema progression, and (iv) mucin hypersecretion. These are known symptoms observed in patients with COPD exacerbations.